Aggregation schemes for k-cycle AMG - Emans, Maximilian (Proceedings of the Conference Algoritmy, 2015)
We examine dierent aggregation schemes for k-cycle AMG. With real-life examples from computational  uid dynamics, we conrm that using aggregates of mainly four nodes results in very ecient methods. However, we show also that the k-cycle aggregation AMG in its known form becomes even more ecient, if simpler aggregation schemes skipping the explicit calculation of intermediate coarse-grid operators are employed.